The meaning extension of Raja : from King of a Nation to King of Pop (Pengembangan makna Raja: daripada Raja sebuah Kerajaan kepada Raja Pop) - Nor Hashimah Jalaluddin,; Ruzy Suliza Hashim,; Zaharani Ahmad, (Fakulti Sains Sosial dan Kemanusiaan, 2011)
Malay kingdom is ruled by ‘RAJA’ (King). Historically, there is an evidence of a treaty among Demang Lebar Daun and Seri Tribuana on the terms of a sovereign, wise and just ruler (Sulalatus Sulatin, 1612). Since then, Malacca has stood up as a very strong, powerful and in control of the Malay Archipelago under the rules of RAJA. Consequently, over the years Malacca has in contact with the Dutch, British, Chinese, Arabs, Indians and many others for their businesses. Apart from the trading activities, the contact has a positive impact to the Malay language itself. One of them is more loanwords has absorbed into the Malay language. Nevertheless, the invasion of British under the Pangkor Treaty (1874) and the amendment of article 23(1) and article 181 (2) in Federal Constituition 1993, have caused the sovereignty and dignity of RAJA reduced to Malay customs and religion only. Since then, the word RAJA is no longer confined to king that rules the nation. Apparently, this development has an impact to the meaning extension of ‘RAJA’ linguistically as well. The meaning of ‘RAJA’ has extended to the name of places (Kampong Raja), organization (Polis di Raja), title (Raja SMS), game (Raja Hitam) and metaphorical expressions (Raja Sehari). Based on 5 million data bank of the classical and modern Malay corpus, this paper attempts to analyze the meaning extension of ‘RAJA’. Interestingly, the meaning extension of RAJA is semantically motivated and well structured